(Re)Habilitar_ O Bairro do Cerco - Patrick Alves Costa (2021)
This dissertation aims to analyze and understand the set of popular houses in the neighborhood of Cerco, designed under the responsibility of the Improvement Plan of the city of Porto and, through its interpretation, suggest possible paths of redesign for the recovery of a built set that is far from being able to respond to contemporary needs. The existing weaknesses result from the parameters used at the time. Given the urgency of response and necessary construction economy (given the current situation), these sets were irreparably conditioned. Relegated the quality was compromised to the healthy experience of the neighborhood in two nuclear spheres: housing and urban system. Housing, as an operational mechanism of the stage of individual and family life. The minimal habitation, rigid and pragmatic, modern concept, widespread standards as 'habit machine', which does not provide the triggering of rich and diverse family dynamics. The second aspect is the relationship with the city and the urban composition system of the neighborhood, or the lack of it, which conditions the internal and external social life of the whole. The 'modern' ideals, asymmetrical to the traditional urban form, represented a rupture that changes the way space is interpreted and appropriate, promoting a disintegration of the sets with the surrounding urban form. This makes it impossible to offer quality of life to the resident community and to promote a harmonious dissolution and coexistence of the whole with its scouting. These critical tissues have been the target of several interventions, however these are slight to achieve the desired results.